2009
DOI: 10.1016/j.chom.2009.06.008
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for RIG-I in Toll-like Receptor-Stimulated Phagocytosis

Abstract: Retinoic acid-inducible gene-I (RIG-I) plays an important role in antiviral response by recognizing double-stranded RNA. Here we demonstrate an unanticipated role of RIG-I in Toll-like receptor (TLR)-stimulated phagocytosis. Stimulation with lipopolysaccharide (LPS), a ligand of TLR4, induced the expression of RIG-I in macrophages. Depletion of RIG-I by RNAi or gene targeting inhibited the LPS-induced phagocytosis of bacteria. Cellular processes involved in phagocytosis, such as small GTPase Cdc42/Rac1 activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 46 publications
4
58
0
Order By: Relevance
“…In NACHT-family, mammalian NOD2 was shown to play a key role in antiviral response since NOD2-deficient mice were more susceptible to infection with single stranded RNA, which challenged the idea that NOD2 specifically restricts bacterial infections (Sabbah et al, 2009). Likewise, retinoic acid-inducible gene-I (RIG-I) of RLR family has been identified as a double-stranded RNA (dsRNA) detector (Yoneyama et al, 2004;Kato et al, 2005Kato et al, , 2006; however, RIG-I-deficient mice were also found to be more susceptible to infection with Escherichia coli as compared to wild-type mice (Kong et al, 2009). In the present study, the overexpression of NALPL1 and NALPL2 in ZF4 cells increased the protection against the viral infection.…”
Section: Discussionmentioning
confidence: 92%
“…In NACHT-family, mammalian NOD2 was shown to play a key role in antiviral response since NOD2-deficient mice were more susceptible to infection with single stranded RNA, which challenged the idea that NOD2 specifically restricts bacterial infections (Sabbah et al, 2009). Likewise, retinoic acid-inducible gene-I (RIG-I) of RLR family has been identified as a double-stranded RNA (dsRNA) detector (Yoneyama et al, 2004;Kato et al, 2005Kato et al, , 2006; however, RIG-I-deficient mice were also found to be more susceptible to infection with Escherichia coli as compared to wild-type mice (Kong et al, 2009). In the present study, the overexpression of NALPL1 and NALPL2 in ZF4 cells increased the protection against the viral infection.…”
Section: Discussionmentioning
confidence: 92%
“…It is also documented that RIG-I functions in antibacterial response. Kong et al (2009) found that RIG-I À/À mice exhibited a reduced threshold to the challenge of lethal bacteria Edwardsiella coli [16]. Abdullah et al (2012) reported that RIG-I was able to detect live Listeria monocytogenes infection by recognizing secreted bacterial RNA/DNA [15].…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylated IRF-3/7 are then able to translocate into the nucleus and induce the production of type I IFNs and IFN-stimulated genes (ISGs), contributing to host antiviral immunity [14]. Recently, it has also been reported that RIG-I may recognize secreted bacterial nucleic acids in cytoplasm and function in antibacterial response, in addition to the previously described antiviral roles [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…We have shown that RIG-I localizes to actin-enriched membrane ruffles and positively regulates cell migration (11). Others have also reported that loss of RIG-I inhibits both actin polymerization and actin distribution in macrophages following LPS stimulation (12). Similarly, NOD2 associates with the actin cytoskeleton and regulates cellular signaling in response to actin cytokskeletal modulation (13).…”
Section: Several Families Of Cytoplasmic Caspase-recruiting Domain (Cmentioning
confidence: 99%